2018
DOI: 10.1007/s00261-018-1666-1
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging and clinicopathologic assessment of abdominal wall endometriosis: knocking down the enigma

Abstract: AWE is a challenging clinical entity frequently diagnosed with a significant delay and easily misinterpreted despite multimodality imaging. Familiarity with its radiologic features holds the potential for positively impacting diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…Diagnostic rates on CT and US are low, with undiagnosed endometriosis in 77-100% of the cases, while MRI establishes the correct diagnosis in 75% of the cases [3]. It seems that radiologists are in general not familiar with the spectrum of endometriosis imaging features.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diagnostic rates on CT and US are low, with undiagnosed endometriosis in 77-100% of the cases, while MRI establishes the correct diagnosis in 75% of the cases [3]. It seems that radiologists are in general not familiar with the spectrum of endometriosis imaging features.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, they present as solid, nodular masses, sometimes stellate clearly defined margins [1]. Recent research has confirmed that heterogenous echogenicity is most common, representing the distribution of fibrous and hemorrhagic components, and varying across the menstrual cycle www.srpskiarhiv.rs [1,3]. Internal echogenic spots or thick strands represent the fibrotic tissue component [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations